Application of the Contextual Teaching Learning Method Problem Based Instructure Model Towards the Improvement of the Ability to Make Nursing Care Trenggalek Nursing Study Program - Ixora Ixora; Dewi Wulandari; Rahayu Niningasih (Health Notions, 2020)
The success of improving the quality of human resources through education can be realized, one of which is through the accuracy of the learning process in achieving learning objectives, one of the government's efforts to improve the quality of education in Indonesia is to improve the curriculum from teacher centered learning to student centered learning by using the contextual method. teaching learning model problem based instructor. In essence, using this learning method where students can relate the content of the lesson to the surrounding environment or the real world so that it makes lessons more meaningful and can increase motivation to learn. The success of this method is strongly influenced by the structural stages contained in the PBI CTL model method. Measuring the ability of students with a pre-test in making Askep who got the PBI model of CTL learning, measuring the ability of students with the pre-test in making Askep who did not get the PBI model of CTL learning, measuring the ability of students with the post-test in making Askep who got the PBI CTL learning model, measuring the ability of students by post-test in making Askep who did not get the PBI model of CTL learning. Type of research is quantitative with a quasi experimental design (quasi-experimental), pre-test and post-test approaches with control group . The sample technique with a total sampling is 80 students DIII nursing study program Trenggalek. The instruments used were the nursing care format and the PBI model CTL module. The research results were tested by using paired sample t- test. The pre-test mean value of the ability to make nursing care in the intervention group was 72.45 and in the control group 68.03 while the average posttest score using the PBI model CTL method in the intervention group was 81.48 and in the control group 73.25. There is a significant effect of the PBI model of CTL method in improving the ability to make nursing care. Keywords: contextual teaching learning, problem based instructor, nursing care